2022
DOI: 10.1039/d2se00079b
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle analysis (LCA) and economic evaluation of catalytic fast pyrolysis: implication of co-product's end-usage, catalyst type, and process parameters

Abstract: The present study aimed to highlight the environmental performance and economic analysis of non-catalytic, Al2O3 and Ni/Al2O3 catalyzed pyrolysis to obtain the more environmentally benign and cost-effective process. The study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…are equally significant and cannot be overlooked while selecting any process. Compared with the previous study on a fresh metal-based catalyst (Al 2 O 3 ), the present study utilizing AHNP (Al)-based catalysts showed substantially lesser price due to the utilization of the waste residue for catalyst preparation . Al- and Ni/Al-catalyzed processes showed ∼97 and 66% reduction in operating cost in the base scenario (considering no coproduct utilization), as compared with the corresponding fresh metal-based Al 2 O 3 - and Ni/Al 2 O 3 -catalyzed processes, respectively …”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…are equally significant and cannot be overlooked while selecting any process. Compared with the previous study on a fresh metal-based catalyst (Al 2 O 3 ), the present study utilizing AHNP (Al)-based catalysts showed substantially lesser price due to the utilization of the waste residue for catalyst preparation . Al- and Ni/Al-catalyzed processes showed ∼97 and 66% reduction in operating cost in the base scenario (considering no coproduct utilization), as compared with the corresponding fresh metal-based Al 2 O 3 - and Ni/Al 2 O 3 -catalyzed processes, respectively …”
Section: Resultsmentioning
confidence: 56%
“…15 Al-and Ni/Alcatalyzed processes showed ∼97 and 66% reduction in operating cost in the base scenario (considering no coproduct utilization), as compared with the corresponding fresh metalbased Al 2 O 3 -and Ni/Al 2 O 3 -catalyzed processes, respectively. 15 Sensitivity analysis was performed on the operating cost of noncatalytic/catalytic pyrolysis considering ±20% variation in the values of different parameters such as drying energy consumption, chopping energy consumption, grinding energy consumption, pyrolysis energy consumption, and catalyst loading. It depicts that the operating cost of noncatalytic pyrolysis is highly sensitive to the variation in the values of pyrolysis energy consumption.…”
Section: Process Economics Through Operating Costmentioning
confidence: 95%
See 1 more Smart Citation
“…The combustion of bio-oil also releases a large amount of greenhouse gases (e.g. : CO 2 ) into the air, which traps heat in the atmosphere and causes an increase in the global warming potential and POCP . A warmer atmosphere would influence the occurrence and severity of acid rain.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the global warming potential (GWP) is the amount of heat trapped by a unit of greenhouse gas in the atmosphere . During electricity production, the combustion of fossil fuels takes place to generate the heat needed to power turbines; hence, burning of these fuels results in the production of carbon dioxide (CO 2 ), which is the primary greenhouse gas and is responsible for the increase of the global warming potential . In the present adsorption process, the subprocesses, namely impregnation and pyrolysis, contribute to the higher GWP of 41.5% (9.4 kg CO 2 ) and 19.2% (4.3 kg CO 2 ), respectively.…”
Section: Resultsmentioning
confidence: 99%